Synthesis, Characterization & Antimicrobial Activities of New Isoxazole Substituted Mannich and Schiff Bases of 5-Nitroisatin Analogs - Jithendra, Ch.; Saravanan, G.; Alagarsamy, V.; Panneerselvam, T.; Selvaraj, K.; Parasuraman, P. (Asian Journal of Chemistry, 2020)
A sequence of new isoxazole substituted Schiff base and Mannich base of 5-nitroisatin are synthesized by a multi-step synthesis from 5-nitroisatin. Whole synthesized analogs were characterized using IR, NMR, Mass spectroscopy and microanalyses. All the Schiff and Mannich bases were tested for their antimicrobial potencies against some human pathogenic microorganism using agar well diffusion technique. The relationship between the biological activity and the functional group variation of the Schiff and Mannich bases were analyzed. Standard ciprofloxacin and ketoconazole were used to compare the antimicrobial activities of novel isatin coupled isoxazole derivatives.